A Comparative Analysis of Attempted and Completed School-Based Mass Murder Attacks - Agnich, Laura E. (American journal of criminal justice, 2015)
“School shootings” are rarely studied quantitatively due to the fact that they are relatively rare, albeit powerful events. Therefore, prior research on “school shootings” typically relies on case study methodologies, or involves the use of typologies based on perpetrators’ motivations, their relationships to victims, and/or the total number of victims killed. However, not all cases of multiple-victim homicide attacks that take place in schools involve the use of firearms, and not all school-based multiple-victim homicide attacks result in multiple fatalities, as many such cases are either thwarted in advance by police or fail to result in the intended number of victims due to a variety of factors. The present study compares attempted and completed mass murder and rampage style attacks that have taken place at schools, and further compares incidents involving firearms to those that involve other deadly weapons. Utilizing a database of 282 identified cases of mass murder incidents in schools across 38 nations, incidents’ date and location, the demographic characteristics of perpetrators, weapons used, number of victims, and school contexts are examined and compared.